EDUCATION AND EMPOWERMENT: EDUCATING GIRLS ON DOMESTIC VIOLENCE - Ertürk, Nesrin Oruç (PEOPLE: International Journal of Social Sciences, 2018)
Growing up in the families where domestic violence exists, young girls after a while conceive violence as normal and accept it when they become the victims. If there is not much to save the mothers from abuse then there should be something to be done to save young girls from violence. Being aware of what domestic violence is and how they can protect themselves and even how they can react when they experience violence, can save the lives of many young girls. These girls’ empowerment against violence can be a sign for empowerment for their abused mothers and sisters as well. The main goal of this study is to train high school girls aged between 15-18 about domestic violence and to equip them with knowledge about their rights in the fields of law, health and social life. In this quasi-experimental study, the participants were given a pre-test before the 10 sessions of training and the same test was given as a post-test after the trainings. Apart from that, the study employs focus group interviews with a selected group of participants where the idea was to collect more insights from some of the participants about violence. Results show that these girls have significantly changed their attitudes or beliefs towards violence. According to the results of the focus group interviews, it is evident that there is a growing awareness of and decreasing tolerance towards domestic violence by the participants.